2022
DOI: 10.3390/jpm12020230
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microcirculation Changes in Crohn’s Disease Patients under Biologics, a Potential Biomarker of Severity: A Pilot Study

Abstract: Crohn’s disease (CD) is associated with increased cardiovascular risk and the retinal microcirculation is a reflection of the systemic microcirculation. Is the retinal microcirculation altered in relation to the severity of Crohn’s disease? This cross-sectional case-controlled study was conducted in a university hospital center from November 2020 to February 2021. We prospectively included patients with moderate (biologic therapy) or severe (biologic therapy + peri-anal disease and/or digestive resection) CD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Altered microcirculation in retina has been found in many autoimmune diseases, such as Crohn's disease, ulcerative colitis, and rheumatoid arthritis [38]. Debourdeau et al have shown reduced VD in SRCP and radial peripapillary capillaries and larger FAZ in patients with severe Crohn's disease [38]. These patients had increased FAZ area and reduced VD in radial peripapillary capillaries compared to patients with moderate Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Altered microcirculation in retina has been found in many autoimmune diseases, such as Crohn's disease, ulcerative colitis, and rheumatoid arthritis [38]. Debourdeau et al have shown reduced VD in SRCP and radial peripapillary capillaries and larger FAZ in patients with severe Crohn's disease [38]. These patients had increased FAZ area and reduced VD in radial peripapillary capillaries compared to patients with moderate Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%